The Art of Yangasha in Jianhe County: Symbolic Meaning, Cultural Representation, and Miao Ethnic Minority Developments in the Process of Modernization - Deng, Weiyu; Phanlukthao, Peera (Journal of Cultural Analysis and Social Change, 2025)
This qualitative study investigates the cultural representation and symbolic significance of yangasha art in Jianhe County, Guizhou Province, China, in the framework of ethnic minority modernization. Researchers utilized Terence Hawkes's symbolic theory and Stuart Hall's notion of cultural representation to examine yangasha art, leveraging data from literature review and field research conducted in Jianhe County. Results indicate that the symbolic significance of Yang'asha art facilitates multifaceted cultural expression across various media. Its symbolic importance illustrates an evolutionary rationale across three dimensions: symbolic construction, narrative reconstruction, and value reconstruction. Yang'asha's cultural representation system went through four stages of change: "explanation of natural phenomena → vehicle of ethical values → marker of ethnic identity → modern cultural capital." This study shows how, in the context of modernization, local traditional culture changes and grows artistically through many different forces, including modern media and mass consumption. This research offers theoretical validation for symbolic studies and cultural representation theory, while also contributing academic significance and inspiration for the transition of national intangible cultural heritage from "preservation and conservation" to "regeneration and development."